Increasing the self-sufficiency of a university campus by expanding the PV capacity while minimizing the energy cost - Randrianantenaina Tina Arizo; Le Gal La Salle Josselin; Spataru Sergiu Viorel; David Mathieu (EPJ Photovoltaics)
Microgrids, which promote the production and consumption of renewable energy on site, are a relevant solution to reduce carbon emissions and the price of energy for end users. However, converting an existing building stock into a microgrid powered mainly by renewable energy requires finding a technical and economic optimum while taking into account strong constraints. This work proposes a methodology to achieve this objective on an existing university campus located in La Reunion, a French island in the Indian Ocean. The campus already has three photovoltaic (PV) systems and high-quality measurement data of weather, loads and energy production. The goal of the work is to find an optimal rooftop PV capacity that maximizes campus self-sufficiency while keeping energy price affordable for users. The results do not highlight a unique combination of roofs as a solution to the optimization problem. However, the analysis of possible combinations gives clear rules for defining the total photovoltaic capacity to be installed and selecting the most suitable roofs.